Novel Hydroxytyrosol-Donepezil Hybrids as Potential Antioxidant and Neuroprotective Agents - Costanzo, Paola; Oliverio, Manuela; Maiuolo, Jessica; Bonacci, Sonia; De Luca, Giuseppina; Masullo, Mariorosario; Arcone, Rosaria; Procopio, Antonio (Frontiers in Chemistry, 2021)
It is well-accepted that the endogenous antioxidant protection system progressively decays in elderly people, and that the oxidative stress contributes to different neurodegenerative disorders such as Alzheimer’s Diseases (AD). The lower incidence of AD in countries which feature the Mediterranean Diet was associated to the high consumption of extra virgin olive oil and its polyphenolic fraction, in particular hydroxytyrosol. The protective role of these bio-phenols against oxidative stress, suggested that we combine their antioxidant/free radical scavenging activity with donepezil, an active ingredient which has just been approved for the treatment of AD. Different synthetic strategies were tested to conjugate the two different synthons in good yields. Additionally, a nitro-hydroxytyrosol derivative was synthesized to extend the application to other neurodegeneration inflammatory models. Then, their bioactivity was measured in different chemical and biological tests on a human neuroblastoma cell line (SHSY-5Y). Remarkable results on cell viability and the regulation of the redox state of cells were obtained. All hybrids showed negligible cell death under 1 μM and are stable and non toxic. Reactive oxygen species (ROS) measurements showed that the nitro-hybrid was the more effective one at reducing the ROS amount to physiological values. Then, in light of the bio-metal hypothesis of diverse neurodegenerative disorders, we tested these new compounds on the chelation properties of redox-active metals. The nitro-hybrid was able to chelate all of the tested metal cations, suggesting that we propose it as potential lead compound for a new class of neuroprotective antioxidant agents.